Exploring Local Taxpayer Compliance from an Administrative Law Perspective: The Effects of Tax Literacy, Tax Regulatory Outreach, and Perceived Fairness of Tax Collection in Batam - Juanda Andika Agustian; Rizki Tri Anugrah Bhakti; Dwi Afni Maileni; Indra Sakti (Indonesian Journal Publisher, 2026)
This study examines local taxpayer compliance in Batam from an administrative law perspective by testing the effects of tax literacy, tax regulatory outreach, and perceived fairness of tax collection. The study is motivated by the need to strengthen local own-source revenue, which requires compliance that is not merely formal but also grounded in procedural legitimacy in tax-collection practices. An explanatory quantitative design was employed. A total of 150 questionnaires were collected from registered local taxpayers who actively interacted with the local tax system; after screening for completeness and response consistency, 120 responses were deemed eligible for analysis. The data were analyzed using PLS-SEM (SmartPLS) through measurement-model and structural-model assessment. The results indicate that tax literacy, tax regulatory outreach, and perceived fairness of tax collection all have positive and significant effects on local taxpayer compliance. Among these predictors, perceived fairness of tax collection emerges as the most influential determinant, underscoring the importance of procedural fairness, transparency, and equal treatment in shaping compliance behavior. In addition, the model demonstrates adequate explanatory power, predictive relevance, and overall model fit. The findings suggest that improving local taxpayer compliance requires an integrated strategy combining stronger tax literacy, better-designed regulatory outreach, and reforms in service quality and tax-collection procedures. Theoretically, this study enriches the literature on local tax compliance from an administrative law perspective, particularly with respect to procedural justice and the legitimacy of tax collection. Practically, the findings can inform policy strategies aimed at strengthening taxpayer literacy, designing more effective regulatory outreach, and improving the procedural fairness of tax-collection services in order to enhance compliance and the quality of local tax governance in Batam City.